2008
DOI: 10.1021/bi800102x
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis of Substrate Recognition in Thiopurine S-Methyltransferase

Abstract: Thiopurine S-methyltransferase (TPMT1) modulates the cytotoxic effects of thiopurine prodrugs such as 6-mercaptopurine by methylating them in a reaction using S-adenosyl-L-methionine as the donor. Patients with TPMT variant allozymes exhibit diminished levels of protein and/or enzyme activity and are at risk for thiopurine drug-induced toxicity. We have determined two crystal structures of murine TPMT, as a binary complex with the product S-adenosyl-L-homocysteine and as a ternary complex with S-adenosyl-L-hom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
47
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(55 citation statements)
references
References 31 publications
(53 reference statements)
8
47
0
Order By: Relevance
“…Using this approach, we have characterized the kinetics of 6-MP and 6-TG methylation by TPMT. The results are in excellent agreement with the rates obtained using the radiochemical assay, and the calculated activation energy corresponds to previously reported values [28].…”
Section: The Versatility Of Itcsupporting
confidence: 90%
See 3 more Smart Citations
“…Using this approach, we have characterized the kinetics of 6-MP and 6-TG methylation by TPMT. The results are in excellent agreement with the rates obtained using the radiochemical assay, and the calculated activation energy corresponds to previously reported values [28].…”
Section: The Versatility Of Itcsupporting
confidence: 90%
“…The reaction proceeds through an S N 2 type mechanism [9,27], where the reactive methyl group of SAM is transferred to a nucleophilic center (sulfur atom) on the 6-MP substrate, forming the products SAH and 6-Me MP. A solvent channel provides access to the active site of the enzyme, where the imidazole moiety of bound 6-MP can be oriented to either side [9,28], but formation of product should be possible regardless of the relative orientation. Studies of murine TPMT have shown that after binding of 6-MP, deprotonization of the active thiol tautomeric form is necessary to achieve an activation energy (20 kcal mol −1 ) [27] consistent with the observed reaction rate [28].…”
Section: Tpmt Catalysismentioning
confidence: 99%
See 2 more Smart Citations
“…A chaperone proteindependent, pro teasome-mediated pathway including aggresome formation and protein misfolding (30,31) and auto phagy (32), have been shown to contribute to degra dation of TPMT variant allozymes (12). An alteration at the active site of the enzyme also accounts for the loss-of-function of the TPMT enzyme (33). Altered pro tein quantity, as a consequence of TPMT protein degra dation, is an important mechanism responsible for the functional effects of an inherited variation in the amino acid sequence.…”
Section: One Step Ahead: Quantitative Tpmt Polymorphismsmentioning
confidence: 99%